WOMEN DISCRIMINATION IN NOVEL GINKO BY JUN’ICHI WATANABE - Nuril Hidayati; Januarti Waristiani (JURNAL LITERASI, 2022)
This study analyzes the discussion of women in the Ginko novel. This study uses a qualitative descriptive method designed to describe women's conversations in the Ginko novel. The feminist view used in the Ginko novel by Jun'ichi Watanabe, feminist Women must have the same money as women to succeed in society. This study found that women must have women, where at that time (Meiji era) there were clear boundaries between men and women. The difficulties and debates that occur are due to Ginko's ideals being considered, because he wants to become a doctor. His ability and intelligence are hampered only because he is a woman. It can be concluded in the Meiji era, there were those who opposed women in the Ginko Novel.